1987
DOI: 10.1042/bj2460715
|View full text |Cite
|
Sign up to set email alerts
|

Liver mitochondrial pyrophosphate concentration is increased by Ca2+ and regulates the intramitochondrial volume and adenine nucleotide content

Abstract: 1. The matrix pyrophosphate (PPi) content of isolated energized rat liver mitochondria incubated in the presence of ATP, Mg2+, Pi and respiratory substrate was about 100 pmol/mg of protein. 2. After incubation with sub-micromolar [Ca2+], this was increased by as much as 300%. There was a correlation between the effects of Ca2+ on PPi and on the increase in matrix volume reported previously [Halestrap, Quinlan, Whipps & Armston (1986) Biochem. J. 236, 779-787]. Half-maximal effects were seen at 0.3 microM-Ca2+.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
1

Year Published

1989
1989
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 56 publications
9
65
1
Order By: Relevance
“…Addition of calcium or pyrophosphate, or other agents that raise mitochondrial pyrophosphate, was found to increase the volume of isolated liver mitochondria (Davidson & Halestrap, 1987) and heart mitochondria (Halestrap, 1987). The increased mitochondrial volume stimulates the respiratory chain (by an undefined mechanism) at the level of electron flow into the ubiquinone pool, resulting in stimulation of respiration on many different substrates, particularly fatty acids, in liver and heart mitochondria (Davidson & Halestrap, 1987;Halestrap, 1987). However, it has been found that sucrose (which was used by Halestrap to change the volume of isolated mitochondria) can inhibit respiration of inner membrane vesicles apparently by a viscosity effect on membrane mobility rather than via a volume effect (Chazotte & Hackenbrock, 1988a,b).…”
Section: Application Of Metabolic Control Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of calcium or pyrophosphate, or other agents that raise mitochondrial pyrophosphate, was found to increase the volume of isolated liver mitochondria (Davidson & Halestrap, 1987) and heart mitochondria (Halestrap, 1987). The increased mitochondrial volume stimulates the respiratory chain (by an undefined mechanism) at the level of electron flow into the ubiquinone pool, resulting in stimulation of respiration on many different substrates, particularly fatty acids, in liver and heart mitochondria (Davidson & Halestrap, 1987;Halestrap, 1987). However, it has been found that sucrose (which was used by Halestrap to change the volume of isolated mitochondria) can inhibit respiration of inner membrane vesicles apparently by a viscosity effect on membrane mobility rather than via a volume effect (Chazotte & Hackenbrock, 1988a,b).…”
Section: Application Of Metabolic Control Theorymentioning
confidence: 99%
“…In rat thymocytes cellular respiration rate has been reported to be insensitive to mitochondrial calcium level (Lakin-Thomas & Brand, 1988). In isolated rat brain synaptosomes, the depolarization-induced stimulation of respiration has been found to be calcium-dependent (Patel et al, 1988;Dagani et al, 1989) and calcium-independent (Kauppinen & Nicholls, 1986b;Erecinska & Dagani, 1990 Halestrap, 1989) leading to a rise in matrix [pyrophosphate] (shown in liver mitochondria exposed to micromolar calcium; Davidson & Halestrap, 1987). The raised matrix [pyro-phosphate] is suggested to stimulate K+ uptake into the mitochondria, leading to an increase in mitochondrial volume.…”
Section: Application Of Metabolic Control Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Also hypothyroid mitochondria show lower H + [21] and K + [38] permeability, whereas the C-conformation of the ANT has been found to promote increased permeability of the inner membrane to K + and H + [22,23]; moreover, the decreased permeability in hypothyroid preparations can be rapidly reversed by a single dose of T3 [21] which points to a" mechanism separate from alteration of membrane lipids [39]. Conversion of ANT to the C-conformation has also been shown to promote rapid loss of Ca 2+ from pre-loaded mitochondria [18] and to increase 1 ~tM Ca 2+ uptake [24]. Of relevance in this context is the observation that T3 induces calcium influx into liver cells within minutes and increases respiration and gluconeogenesis with the same kinetics leading to the proposal that, as with glucagon, the signalling involves increased mitochondrial uptake of cytosolic Ca 2+ [40].…”
Section: A Covalently Modified Two-state Model Of the Adenine Nucleotmentioning
confidence: 99%
“…Here we reconsider this conclusion and demonstrate that the velocity of the ANT can be reduced by more than half by nicotinamide addition to isolated mitochondria: further, addition of T3 at 10 pM restored the rate to normal and this was abolished by concomitant addition of nicotinamide. We go on to propose a model based on alteration of the relative proportions of the two distinct conformations of the ANT (see [16]) by ADP-ribosylation which may offer a molecular mechanism not only for the transport effects of T~ but also for those of oxidative stress and ADP-ribosylation inhibitors on Ca 2+ [17][18][19][20], H + [21,22], and K + [22][23][24] transfer across the mitochondrial inner membrane.…”
Section: Introductionmentioning
confidence: 99%